2017
DOI: 10.1021/acsami.7b06130
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photocatalytic, and Antifungal Properties of MgO, ZnO and Zn/Mg Oxide Nanoparticles for the Protection of Calcareous Stone Heritage

Abstract: More recently, the biological colonization of stone heritage and consequently its biodeterioration has become the focus of numerous studies. Among all microorganisms, fungi are considered to be one of the most important colonizers and biodegraders on stone materials. This is why the development of new antifungal materials requires immediate action. ZnMgO nanoparticles (NPs) have several exciting applications in different areas, highlighting as an efficient antimicrobial agent for medical application. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(75 citation statements)
references
References 46 publications
1
71
0
3
Order By: Relevance
“…In particular, Huang et al, further demonstrated that peptide linkages in the bacterial cell wall are physically damaged by the generation of superoxide ions on the surface of nMgO (Huang et al, 2005). Conceivably, nMgO have enormous potential as antibacterial agents, effectively suppressing agricultural bacterial and fungal diseases caused by Ralstonia solanacearum, a medical and foodborne pathogen (Jin and He, 2011;Parizi et al, 2014;Imada et al, 2016;Sierra-Fernandez et al, 2017;Cai et al, 2018a). Nonetheless, investigations on the effects of nMgO on fungal pathogens and on elaborate antimycotic mechanisms have scarcely been reported before (Jin and He, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Huang et al, further demonstrated that peptide linkages in the bacterial cell wall are physically damaged by the generation of superoxide ions on the surface of nMgO (Huang et al, 2005). Conceivably, nMgO have enormous potential as antibacterial agents, effectively suppressing agricultural bacterial and fungal diseases caused by Ralstonia solanacearum, a medical and foodborne pathogen (Jin and He, 2011;Parizi et al, 2014;Imada et al, 2016;Sierra-Fernandez et al, 2017;Cai et al, 2018a). Nonetheless, investigations on the effects of nMgO on fungal pathogens and on elaborate antimycotic mechanisms have scarcely been reported before (Jin and He, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Green chemistry utilizes nontoxic chemicals and environmentally friendly solvents for synthesizing NPs, which clearly shows a different path in eliminating wastes before it is generated. Nowadays, inorganic metal NPs such as MgO and ZnO, Ag, Au, Cu, Cu 2 O and Cu/Cu 2 O are increasingly used as antimicrobials owing to their stability and long shelf life compared with the organic antimicrobial agents. The exploration of nanostructures offers new possibilities in biological context, and owing to the fact that the surface area of particles increases by decreasing particle size, biological activity enhances per given mass in comparison with larger particles …”
Section: Introductionmentioning
confidence: 99%
“…However, there is another type of nanoparticles that are produced by man, known as engineered nanoparticles (ENPs), which are manufactured using different materials such as metal oxides, metals, carbon, polymers and lipids [1]. The potential of nanoparticles (NPs) for conservation of built structures has been established for the consolidation of decayed materials, production of de-polluting surfaces, self-cleaning, surface enhancement or as a biocide to reduce biodeterioration [2][3][4][5]. Titanium dioxide (anatase) has been employed for many years [6,7] and in some respects has become the gold standard for self-cleaning surfaces.…”
Section: Use Of Nanoparticles In the Protection Of Cultural Heritage mentioning
confidence: 99%